Taking Risks and Survival Jobs: Foreign-Born Workers and Work-Related Injuries in Australia - Reid, Alison; Lenguerrand, E.; Santos, I.; Read, U.; LaMontagne, A.; Fritschi, Lin; Harding, S. (Elsevier BV, 2014)
Higher rates of work-related injuries (WRI) have been reported among foreign-born workers in many countries, but little is known about the situation in Australia, which initially had large waves of European followed by Asian migration and where the recruitment of skilled migrants has dominated recently. The aim of the study was to examine WRI among foreign-born workers in Australia. This was a two phase mixed methods study. The first stage used the 2005/6 and 2009/10 Australian national Multi-Purpose Household Survey (MPHS) information on WRI occurring in the previous year (N = 36,702). Logistic regression examined the relationship between WRI and country of birth, adjusting for period of arrival in Australia, age, sex, industry and working conditions. Next, 92 purposively sampled foreign-born workers participated in individual interviews (n = 17) or focus groups (n = 75). Workers were sampled via community organisations, trade unions or churches. A concurrent thematic analysis was conducted. Analysis of the MPHS showed that country of birth was generally not associated with a higher reporting of WRI and compared with Australian-born workers, those from Oceania reported less WRI. Key themes from the interviews suggest that understanding of Occupational Health and Safety (OH&S) differed by community integration and cohesiveness. Precarious work, cultural factors and the demands of production may preclude workers from reporting incidents. Quantitative findings from the MPHS point to higher risks related to area of work rather than country of birth. However qualitative findings suggest there may be some under-reporting of WRI among migrants to Australia.